THE DESIGN AND IMPLEMENTATION OF AN EDUCATIONAL MULTIMEDIA INTERACTIVE OPERATION SYSTEM USING LECTORA INSPIRE - Wibawa, Setya Chendra; Harimurti, Rina; Anistyasari, Yeni; Sumbawati, Meini Sondang (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2017)
The objective this research to produce a valid interactive learning tool and practice based on learning media Lectora Inspire; knowing the student response against the learning tool, and knowing the student learning outcomes after using Lectora inspire learning media. Research and development of the research method using ADDIE model. Research with the learning media to be tested against the 32 student X level of Vocational High School and the subject is operation system. Research analysis results obtained through student response and question form reserved post-test. Validation of results obtained through validation by the validator which consists of one lecturer of Informatics and two teachers in a primary against 83.3% of Planning of Learning validation, validation against reserved posttest of 93.9% and validation against the media learner Lectora inspire of 100%, the results of all the validations that meets the criteria for applied research. The percentage of the average student response against Lectora media inspire 85.9%. While the percentage of student learning results expressed satisfaction with the presentation of graduation of 84.375% means it can be inferred that the media Lectora inspire gets good results and media can be said to be effective as a learning tool to supporting study students.